The changing role of health‐oriented international organizations and nongovernmental organizations. (3rd August 2015) - Okma, Kieke G.H.; Kay, Adrian; Hockenberry, Shelby; Liu, Joanne; Watkins, Susan
Summary: Apart from governments, there are many other actors active in the health policy arena, including a wide array of international organizations (IOs), public‐private partnerships and non‐governmental organizations (NGOs) that state as their main mission to improve the health of (low‐income) populations of low‐income countries. Despite the steady rise in numbers and prominence of NGOs, however, there is lack of empirical knowledge about their functioning in the international policy arena, and most studies focus on the larger organizations. This has also caused a somewhat narrow focus of theoretical studies. Some scholars applied the 'principal‐agent' theory to study the origins of IOs, for example, other focus on changing power relations. Most of those studies implicitly assume that IOs, public‐private partnerships and large NGOs act as unified and rational actors, ignoring internal fragmentation and external pressure to change directions. We assert that the classic analytical instruments for understanding the shaping and outcome of public policy: ideas, interests and institutions apply well to the study of IOs. As we will show, changing ideas about the proper role of state and non‐state actors, changing positions and activities of major stakeholders in the (international) health policy arena, and shifts in political institutions that channel the voice of diverging interests resulted in (and reflected) the changing positions of the health‐oriented organizations‐and also affect their future outlook. Copyright © 2015 John Wiley & Sons, Ltd.